The Effect of Defibrinogenation on Pulmonary Embolism in Dogs - Meissner, Alfred G.; O’Sullivan, Gerald; Macbeth, Robert A. (Thrombosis and Haemostasis, 1976)
The role of fibrinogen in the pathophysiology of pulmonary embolism is not clearly understood. A study was therefore performed in order to determine the effect of defibrinogenation on the sequelae of experimental pulmonary embolization in the canine model. Total defibrinogenation was achieved by treating 15 dogs with Defibrase over a period of three days, and these were studied and compared with 15 control animals. The embolus was produced by injection of a homologous clot into the superior vena cava. A 27 per cent mortality rate was observed after embolism in the control group, but there were no deaths in the Defibrase-treated animals. Hemodynamic and pulmonary gas exchange disturbances occuring in the control group were more severe than those in the treated group and were associated with marked fibrinogen consumption. It is suggested, therefore, that defibrinogenation reduces the mortality and severity of the pathophysiological changes associated with pulmonary embolization probably by inhibition of pulmonary intravascular coagulation and by changing the rheological properties of the blood.